COMPARISON OF METHODS FOR OBTAINING GENETIC DIVERSITY FOR BREEDING WINTER-HARDY WHEAT IN SIBERIA - V. E. Kozlov (Вавиловский журнал генетики и селекции)
High winter hardiness requires two features: (1) a duration of deep rest comparable to the duration of wintering and (2) high frost resistance. An interdisciplinary approach to studying the mechanisms governing the formation of winter hardiness permits one to develop new methods for increasing genetic diversity, to improve well-known ones, and to compare their efficiencies. Such diversity, in particular, is essential for breeding wheat varieties that would meet the conditions of Siberia. Treatment of shoots of winter varieties with gibberellin A 3 yielded families (lines) with 85–100 % survival under deep snow cover in the foreststeppe zone. The survival of original varieties under the same conditions was lower by an order of magnitude. Gibberellin stress in two consecutive generations induced a long deep rest in some survivors, comparable to the duration of wintering, which ensured high survival of their offspring. These changes were inherited. The harder was the selection for the duration of deep rest in «gibberellic» lines, the higher proportion of them was constituted by highly frost-resistant forms that survived under conditions of poor snow cover in the steppe. When both parents had at least one component of high winter hardiness, the crosses yielded the highest proportion of highly frost-resistant forms. Inbred clones of intermediate wheatgrass Agropyron glaucum were good donors of both components of winter hardiness when crossed to wheat. Hereditary changes in wheat accessions in two consecutive generations both in the forest-steppe under the influence of gibberellins and in the steppe under the effect of moderate to severe frosts are likely to have a regulatory epigenetic nature.